Markers of quality and genuineness of commercial extra virgin sacha inchi oils - Chasquibol Silva, Nancy Ascención (2016)
This work tackles the study of the quality and authenticity of oils labeled and commercialized as extra virgin sacha inchi oil. Major and minor components as triglycerides, fatty acid methyl esters, tocopherols, sterols and hydrocarbons are determined as well as other physicochemical parameters (density, viscosity, acidity and peroxide value). The results showed that some of the commercialized oils do not fulfill the basic requirement established in the regulation such as the content of a-linolenic acid, higher than 44.7 or 55.0% in the cases of P. volubilis and P. huayllabambana, respectively. The calculated stigmasterol/campesterol ratio for genuine sacha inchi oils should be around 4, however not all commercial oils analyzed comply with this requirement. The presence of the flavons sesamin and sesamolin indicates the addition of compounds from sesame oils. Finally, some of the commercial oils showed to contain trans fatty acids although this was not accompanied by the sterene hydrocarbon presence.